2021
DOI: 10.3390/ijms222112003
|View full text |Cite
|
Sign up to set email alerts
|

Description of Release Process of Doxorubicin from Modified Carbon Nanotubes

Abstract: The article discusses the release process of doxorubicin hydrochloride (DOX) from multi-wall carbon nanotubes (MWCNTs). The studies described a probable mechanism of release and actions between the surface of functionalized MWCNTs and anticancer drugs. The surface of carbon nanotubes (CNTs) has been modified via treatment in nitric acid to optimize the adsorption and release process. The modification efficiency and physicochemical properties of the MWCNTs+DOX system were analyzed by using SEM, TEM, EDS, FTIR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…For example, the release of methotrexate and cyclophosphamide fits the Higuchi and Korsmeyer–Peppas kinetic models, respectively, depending on pH and temperature. 51 Chudoba et al 52 reported that the best-fit release kinetics of doxorubicin from modified CNTs are due to Korsmeyer–Peppas/Ritger–Peppas kinetics (power-law model) and release controls by Fickian diffusion. Other studies have shown different kinetic models for releasing drugs from CNTs, such as the release of the natural agent silibinin from MWCNTs, which best fits pseudo-second-order kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the release of methotrexate and cyclophosphamide fits the Higuchi and Korsmeyer–Peppas kinetic models, respectively, depending on pH and temperature. 51 Chudoba et al 52 reported that the best-fit release kinetics of doxorubicin from modified CNTs are due to Korsmeyer–Peppas/Ritger–Peppas kinetics (power-law model) and release controls by Fickian diffusion. Other studies have shown different kinetic models for releasing drugs from CNTs, such as the release of the natural agent silibinin from MWCNTs, which best fits pseudo-second-order kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…[92] Additionally, several mathematical operations include zero, first and second-order kinetics, Higuchi, Hixson-Crowell, Ritger-Peppas/Korsmeyer-Peppas (power-law model), and Weibull can be applied to illustrate the release mechanism. [93,94] The zero-order model has a constant drug release rate across time, whereas in the first-order model, the release of the drug is directly proportional to the drug concentration. [94] The Higuchi model explains the release rate as a function of the square root of time, and its generalized model is termed the Korsmeyer-Peppas model.…”
Section: Antifungal Drug Releasementioning
confidence: 99%
“…If the HIF-1α content is low, it suppresses the immune function, cartilaginous tissue formation, wound healing, etc. [ 13 , 14 , 15 , 16 ]. If the HIF-1α content is high, it points to oncological or cardiovascular diseases: hypoxia, strokes, heart attacks, pulmonary hypertension, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increasing or decreasing the HIF-1α content through pharmacological intervention can help to treat many types of diseases [ 12 , 13 , 14 , 15 ]. The concentration of a drug released from its carrier varies linearly or exponentially with time, which is normally described by the diffusion equation [ 16 , 17 ]. However, as has been found experimentally, wavelike kinetics of drug release are also possible [ 18 ].…”
Section: Introductionmentioning
confidence: 99%